2009
DOI: 10.1093/pcp/pcp065
|View full text |Cite
|
Sign up to set email alerts
|

Spodoptera littoralis-Induced Lectin Expression in Tobacco

Abstract: The induced defense response in plants towards herbivores is mainly regulated by jasmonates and leads to the accumulation of so-called jasmonate-induced proteins. Recently, a jasmonate (JA) inducible lectin called Nicotiana tabacum agglutinin or NICTABA was discovered in tobacco (N. tabacum cv Samsun) leaves. Tobacco plants also accumulate the lectin after insect attack by caterpillars. To study the functional role of NICTABA, the accumulation of the JA precursor 12-oxophytodienoic acid (OPDA), JA as well as d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 66 publications
0
29
0
1
Order By: Relevance
“…Transcript levels for the tobacco lectin are upregulated after jasmonate treatment and insect herbivory (Chen et al, 2002;Vandenborre et al, 2009). Presumably, Nictaba acts as a signalling molecule in response to stress, resulting in altered gene expression, caused by the interaction with O-GlcNAc (O-linked b-D-N-acetylglucosamine)-modified histones (Delporte et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Transcript levels for the tobacco lectin are upregulated after jasmonate treatment and insect herbivory (Chen et al, 2002;Vandenborre et al, 2009). Presumably, Nictaba acts as a signalling molecule in response to stress, resulting in altered gene expression, caused by the interaction with O-GlcNAc (O-linked b-D-N-acetylglucosamine)-modified histones (Delporte et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…68 JA induced the expression of NICTABA lectin in tobacco leaves. 68,69 Induction of NICTABA by herbivores infestation including S. littoralis, Manduca sexta L. and Tetranychus urticae Koch has been reported in tobacco plants. 69 Expression of a mannose-binding jacalin-like lectin called Hessian fly, Mayetiola destructor (Say) responsive protein 1 (HFR1), and two chimerolectin-like proteins called HFR2 and HFR3 have been reported to be induced by the larvae of Hessian fly, M. destructor in wheat.…”
mentioning
confidence: 99%
“…68,69 Induction of NICTABA by herbivores infestation including S. littoralis, Manduca sexta L. and Tetranychus urticae Koch has been reported in tobacco plants. 69 Expression of a mannose-binding jacalin-like lectin called Hessian fly, Mayetiola destructor (Say) responsive protein 1 (HFR1), and two chimerolectin-like proteins called HFR2 and HFR3 have been reported to be induced by the larvae of Hessian fly, M. destructor in wheat. 70,71 Differences in feeding behavior of insects results in expression of different lectins, e.g., larvae of the fall armyworm, S. frugiperda induced HFR2, but not HFR3 expression while the phloem-feeding bird cherry-oat aphid, Rhopalosiphum padi Koch, induced HFR3 and HFR2, but latter was expressed much later (12 d) than the former (24 h).…”
mentioning
confidence: 99%
“…All these lectins are classified into twelve lectin families . Conditions that can induce lectin expression include salt stress (Zhang et al, 2000), pathogen infection (Qin et al, 2003), jasmonic acid treatment (Lannoo et al, 2007) and insect herbivory (Subramanyam et al, 2008;Vandenborre et al, 2009a, b). In contrast to the classical lectins that are usually stored in vacuoles, the inducible lectins often locate to the nucleus and the cytoplasm of the plant cell.…”
Section: What Are Lectins?mentioning
confidence: 99%
“…Lannoo et al (2007) have shown that the expression the tobacco lectin called Nictaba was induced upon jasmonate treatment. More recently, Vandenborre et al (2009a, b) showed that Nictaba-expression was also induced by feeding of S. littoralis, which in turn results in elevated jasmonate levels in the leaf tissue. The effects of this tobacco lectin on insect growth and development are under investigation in our laboratory and reveal insecticidal activity of this inducible tobacco lectin (Vandenborre et al, 2009c).…”
Section: Lectins With Inducible Expressionmentioning
confidence: 99%